THE ROLE OF PAMONG PRAJA UNIT HANDLING ILLEGAL ADVERTISEMENT IN SUKABUMI CITY - Ayyul Hizba, Muhammad Ihsan; Amirulloh, M. Rijal; Mulyadi, Andi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The aim of this research is to determine the role of the civil service police unit handling illegal billboard control in Sukabumi City.the penomena that researchers found in the field were control that was not in accordance with the supervisory function, a reduction in local revenue from advertising tax, and a lack of quality of satpol-pp service personnel.the researcher uses role theory according to Achmad Santosa.The role dimensions used are role as a policy, role as a strategy, role as a communication tool, role as a tool for resloving disputes,and role as therapy.The research method used in qualitative with a narrative approach.and the snowball sampling technique strategy was used to identify 5 informants.Data was obtained through observation, interviews and documentation.The procedure for testing the validity of the data was carried out using source triangulation and techniques.The results of the research revealed that the role of the satpol-pp service has not beenable to carry out appropriate control with a supervisory function, reduction of local revenue from advertising tax, and lack of quality of satpol-pp personnel based on emplyoyment status employment level.so that regulation of advertisements can be carried out well,the Sukabumi City satpol-pp service needs to improve ordering, Supervision, Communication, Coordination, and Collaboration.